Implementasi Pasal 106 Peraturan Daerah Kota Pekanbaru Nomor 07 Tahun 2012 tentang Retribusi Izin Mendirikan Bangunan Terhadap Pemilik Ruko yang Menambah Bangunan Melewati Garis Sempa dan Bangunan (GSB) di Kota Pekanbaru - Rahmadani, Puji Bulan; Indra, Mexsasai; HZ, Evi Deliana (Jurnal Ilmiah Wahana Pendidikan, 2024)
Local governments have an interest in building permits. In order to carry out the construction of a building, whether carried out by individuals or private parties who have business functions, they are required to have a Building Construction Permit (IMB) and this permit is needed to fulfill one of the construction requirements. However, since the Job Creation Law came into force, Building Construction Permits have changed to Building Construction Approvals. One of the provisions in building permits is the Building Boundary Line (GSB). For Jalan HR Soebratas, the building must have a GSB of 40 meters from the road axle. In reality, there are still many buildings, especially shophouses, adding buildings beyond the building boundaries. Some of the consequences are traffic jams because land that should be used for parking is used. Based on Pekanbaru City Regional Regulation Number 07 of 2012 concerning Building Permit Levy, specifically in Article 106, there are administrative sanctions imposed on violators of the Regional Regulation, especially shop owners who add buildings beyond the GSB. From the results of the research that has been carried out, implementation has gone quite well. This is because the relevant agencies move through reports or complaints.